Analisis Perataan Penghasilan (Income Smoothing): Faktor-Faktor yang Mempengaruhi dan Kaitannya dengan Kinerja Saham Perusahaan Publik di Indonesia - Hanna Meilani Salno; Zaki Baridwan (The Indonesian Journal of Accounting Research, 2013)
This research is designed to examine the income smoothing in Indonesia. Income smoothing can be defined as a means used by management to diminish the variabiity of a stream of reported income numbers relative to some perceived target stream by the manipulation of artificial (accounting) and real (transactional) variables (Koch, 1981). Two main isues investigated in this research were factors influencing income smoothing and the linkage between income smoothing and performance (return and risk) of public companies’ stocks in Indonesia.Seventy four listed companies in Jakarta Stock Exchange (JSX) selected using (purposive) judgement sampling method were used as research sample. The sample was then clasified into smoother and non smoother using Eckel’s model (1981). Eckel’s clasification uses three kinds of income as research objects: operating income, income before tax, and income after tax (net income). The result showed that there was income smoothing practiced by companies listed in JSX.Common and special statistical tests according to the hypothesis were used in this research. Common statistic includes descriptive statistics, normality data tests (with One Sample Kolmogorov Smirnov Test) and population tests (with Mann-Whitney U Test and t Test). All kinds of common statistical tests concluded that some data was distributed normally and the rest was not, eventhough those data came from the same population.The first hypothesis examined whether size, net profit margin, industrial sectors, and winner/losser stocks influenced income smoothing. Logistic regression was used to test this hypothesis and concluded that the first hypothesis cannot be rejected. The first conclusion stated that all factors hypothesized were not influence income smoothing. The second hypothesis examined whether there was return difference between smoother and non smoother. This hypothesis was tested with Independent Sample t Test and concluded that there was no return difference between smoother and non smoother. The third hypothesis examined whether there was risk difference between smoother and non smoother. This hypothesis tested with Independent Sample t Test. The last conclusion stated that there was no risk difference between smoother and non-smoother.